Medical Technologies in Neurosurgery - Nimsky, C.; Fahlbusch, R.; SpringerLink (Online service) (Vienna : Springer Vienna, 2006)
The tremendous progress evolving in medical technologies in recent years increasingly influences our daily neurological practice. Ethical aspects in the application of technologies from differing viewpoints are discussed in detail. Additionally, typical examples for the application of medical technologies in the operating room include image processing, robotic devices, and intraoperative imaging are clearly presented.
Bioethics, technology and human dignity: the Roman Catholic viewpoint -- Robotics and artificial intelligence: Jewish ethical perspectives -- Ethics in the use of new medical technologies for neurosurgery: (3z(BIslamic viewpoint(3y (B-- Shadow of Buddhism and Shintoism in neurosurgical practice in Japan -- Current status of medical technology -- Uncertainty in diffusion tensor based fibre tracking -- Robotics in neurosurgery: which tools for what? -- Computer- and robot-aided head surgery -- Telecontrolled micromanipulator system (NeuRobot) for minimally invasive neurosurgery -- Usefulness of intraoperative magnetic resonance imaging for glioma surgery -- Intraoperative magnetic resonance imaging in neurosurgery: the Brigham concept -- Intraoperative high-field MRI: anatomical and functional imaging -- Intraoperative MR imaging: preliminary results with 3 tesla MR system.s
Keywords: Medicine; Interventional radiology; Neurosurgery; Minimally invasive surgery; Medical ethics; Medicine & Public Health; Neurosurgery; Minimally Invasive Surgery; Interventional Radiology; Theory of Medicine/Bioethics.; Electronic books